Evaluating the efficacy and safety of electro-acupuncture in patients with antipsychotic-related constipation: protocol for a randomized controlled trial - Fang-Ting Yu (BMC, 2021)
Abstract Background Constipation is known as a common adverse effect of antipsychotics. Advice for its management remains inadequate. This study is designed to investigate the efficacy and safety of electro-acupuncture (EA) for antipsychotic-related constipation. Methods This is a single-centric, parallel-group, randomized controlled trial with blinded participants, outcome assessor, and statistician. One hundred twelve participants will be randomly assigned into the EA group or sham acupuncture (SA) group in a 1:1 ratio. The study will last for 22 weeks for each participant, including a 2-week baseline assessment period, an 8-week treatment period, and a follow-up for 12 weeks. The primary outcome is the change of mean weekly complete spontaneous bowel movements (CSBMs) during weeks 1 to 8 from baseline. Secondary outcomes include the change from baseline of mean weekly CSBMs during the follow-up period, mean weekly spontaneous bowel movements (SBMs), overall CSBM response rate, scores on Bristol Stool Form Scale (BSFS), straining level, Patient Assessment of Constipation Symptoms (PAC-SYM), Patient Assessment of Constipation Quality of life questionnaire (PAC-QOL), and Brief Psychiatric Rating Scale (BPRS). Adverse events and medicine use will be recorded as well. Discussion The study is designed based on a rigorous methodology to evaluate the efficacy and safety of EA for antipsychotic-related constipation. The finding will be published in peer-reviewed journals as reliable evidence. Trial registration ClinicalTrials.gov ChiCTR2000032582. Registered May 3, 2020, with the Chinese Clinical Trial Registry.